GENDER DISCRIMINATION IN DRAGON AGE: ORIGINS GAME NARRATIVE - Willy Novianto Wuntu; Abdurrosyid Abdurrosyid (Department of English Literature, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This article explores the narrative in Dragon Age: Origins, a video game released in 2009 that was developed by BioWare and published by Electronic Arts. This research aims to show how this game’s narrative can be experienced both by passively watching and actively involving the player’s input through the video game narrative forms, according to Sebastian Domsch, while showing gender issues through them. This research uses qualitative analysis to explain the video game narrative. The result is that Dragon Age: Origins shows that this game can be experienced both passively and actively through the video game narrative forms, which are passive and active nodal forms. It also shows discrimination towards women in its narrative with the women treated mainly as a victim and the sexual violence against them being used as a way to bring drama to the game’s narrative.